The Behaviour of Confined Granular soil loaded by a square footing - Zangana, Dhiaadin Bahaadin Noori (Sulaimani Journal for Pure and Applied Sciences, 2015)
This research involves the behaviour of confined granular soil supported by a square footing. A series of bearing capacity tests were carried out on a small-scale laboratory model, which filled with sand, placed in a dense state and confined with UPVC cell. The response of an unconfined state was measured in the beginning, and then compared with the confined sand. The studied variables included the cylinder height and diameter, the depth of the footing to the top of the cylinder and the embedded depth of the footing. The test results indicated that the soil confinement resists lateral displacement of sand underneath the footing, which is leading to a significant improvement for the response of the footing. The curves of load-settlement generally showed the same trend in all the cases. Failure was considered as a settlement, which was equal to 8% of the total footing width. Also, the recommended optimum cell height, diameter, footing depth to the top of the cylinder and the embedded depth of footing that give the maximum bearing capacity improvement were presented and discussed. According to the present research results, a conclusion based on the soil confinement role and found to be notably increased the bearing capacity and stiffness. Furthermore, a modification of load–settlement behaviour of the sub grade sand was also gained.
Keywords: Square Footing; Bearing Capacity; LoadSettlement Behaviour; Granular Soil; Confinement